NOS BASTIDORES DA PALAVRA - Fussieger, Luciano (Organon, 2007)
The present article is the result of a compilation of ideas which were extendedly developed in the mandatory final paper for UFRGS to obtain the qualification of undergraduate teacher in languages and literature. The subject are the narratives (tales) that come from the Brazilian oral tradition and which are crystalised by writing. Such narratives are intended to be affiliated to the family of dramatic texts (through comparisons with some theatrical expressions as the Commedia dell’Arte), taking them out of the field of comparison with narrative texts, fact which has always reinforced the idea of lower aesthetic value of this kind of literary manifestation. Through this new theoretical perspective we try to demonstrate how the tales that come from the oral tradition are embedded with some theatrical characteristics, which arouse only in the contexts in which the tales are fully successful, i. e. performatic contexts. In this sense, we defend the idea that such tales, when written, are formally close to theatrical texts.